(untitled) (Sociologisk Forskning, 1997)
Following a thread of Ariadne - a contribution to the understandingof the dialectic between social responsivitet and asocial responslöshet The following article addresses the question of how, at an elementary level, Asplund’s concept of asocial responslöshet (asocial non-responsiveness) can be distinguished from his different forms of social responsivitet (social responsiveness). The article’s point of departure is the absence of a discussion in Asplund’s book Det sociala livets elementära former concerning that which characterizes the elementary forms of asocial responslöshet. This article attempts to shed light on the relation between the elementary and the advanced - learned - levels by virtue of an imaginary though empirically possible example. The main question hereby addressed is in other words: How can one describe asocial responslöshet on an elementary level?